Human Health Risk of Glyphosate Residues in Rice (Oryza sativa) and Beans (Phaseolus vulgaris) In Gombe State, Nigeria in an Era of COVID-19 Pandemic (Journal of Environmental Bioremediation and Toxicology, 2022)
Samples of beans and rice were collected from five Local Government Areas (LGAs) of Gombe State for the quantitative determination of glyphosate residues. The residue extraction was performed using acetonitrile/water (50/50%) solution and the extracts were injected into the injection block of gas chromatography in tandem with a mass spectrophotometer for separation and quantification. The concentrations of glyphosate in bean samples ranged between 0.0164 mg/kg and 0.0508 mg/kg higher than the residues found in rice samples between 0.0175 mg/kg and 0.0434 mg/kg. The highest concentration of glyphosate residues in beans was 0.0508±0.01 mg/kg from Gombe LGA while the rice sample from Akko LGA was highest with 0.0434±0.02 mg/kg. Both samples in all the LGAs were found to be lower than their respective Maximum Residual Limits (MRLs) and lower than the Acceptable Daily Intake (ADI) of 0.5mg/kg/day. Health Index, HI < 1 was obtained in all samples; indicating that the residues in the grains do not pose any threat to the exposed population. However, the Cancer Risk Index, CRI for children were 7.32x10-4 and 4.090x10-4while those for adults were 9.140x10-2 and 5.120x10-4 for beans and rice respectively. The TCRI for children and adults were 1.140x10-3 and 6.030x10-4 respectively. These are indications that the exposed population is at high risk, with the children more susceptible, probably due to low body weight. The study, therefore, suggests strict monitoring of the use of glyphosate-based herbicides to curtail or minimize the risk of possible bioaccumulation in the body and also calls on further studies on human urine and blood samples of farmers within the study area for further toxicological studies.
Keywords: health risks; Glyphosate Residues; Health index; Rice; Beans